Faktor yang Mempengaruhi Alih Fungsi Lahan Daerah Resapan Air Kecamatan Cimenyan - Bagas Wijayakusuma (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Many water catchment areas (DRA) have been converted into built-up areas, one of which is the Cimenyan District. Looking at the related problems, the authors argue that